2015
DOI: 10.1002/uog.14780
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of simulation‐based ultrasound training on clinical performance: a randomized trial

Abstract: ObjectiveTo study the effect of initial simulation-based transvaginal sonography (TVS) training compared with clinical training only, on the clinical performance of residents in obstetrics and gynecology (Ob-Gyn), assessed 2 months into their residency.MethodsIn a randomized study, new Ob-Gyn residents (n = 33) with no prior ultrasound experience were recruited from three teaching hospitals. Participants were allocated to either simulation-based training followed by clinical training (intervention group; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 40 publications
2
95
1
3
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of the excluded papers, five had heterogeneous study groups which included or focused on more senior clinicians, three did not objectively assess the study group post-intervention, and two did not have a practical image acquisition component to the assessments.…”
Section: Resultsmentioning
confidence: 99%
“…), none had previously performed the fetoscopic laser procedure for TTTS. In the group of experts, 5/11 (45%) had performed > 100 procedures with a median of 10 procedures (range, [8][9][10][11][12][13][14][15][16][17][18][19][20] annually. The demographics of the participants are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Trials have shown lasting effects on learning imparted from simulation ultrasound training with better clinical performance in students. 52 With advancement in technology, the ultrasound simulators are likely to become more complex and provide detailed evaluation not possible otherwise. Ultrasound simulators and task trainers can now be used to accelerate the learning process, provide exposure to cases that may not be available during limited clinical rotations, and permit residents to practice various ultrasound-guided procedures without any potential risk to patient safety.…”
Section: Scenario Trainingmentioning
confidence: 99%